Restrictive Cardiomyopathy or Constrictive Pericarditis: An Unresolved Conundrum. Issue 3 (May 2018) - Ho, Gregory; Peng, Ed; Hermuzi, Antony; Hasan, Asif
Cardiomyopathy may have a variety of causes and may lead to significant morbidity. Often, there is no "perfect" treatment. New investigative techniques may add insight but retain the possibility of uncertainty. The distinction between restrictive cardiomyopathy and pericardial constriction may be challenging, particularly when considering the incidence of these entities. This distinction may significantly impact patient management and this is becoming increasingly important in the context of donor organ austerity. We present a case of a 17-year-old male to illustrate the overlap highlighting this debate and our subsequent management.